Experimental Evidence on Bargaining Power Within Couples - Miriam Beblo; Denis Beninger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We conducted an experiment on the nature of income sharing within 95 established couples in Germany. In a first step, the partners revealed their individual preferences by making consumption choices independently. In a second step, decisions were taken jointly over five different rounds with varying resource allocations between the partners. From this design we are able to derive a female bargaining power index without structural restrictions, reflecting the sharing rule within the couple. We observe this index to increase significantly with the female partner s money allocation. This effect is robust to the inclusion of socio-economic, distributional and behavioural features of the couple.
Keywords: D13; C92; C71; 330